RANCANG BANGUN KOTAK PENYIMPANAN UANG DENGAN VOICE RECOGNITION BERBASIS MIKROKONTROLER - xu, Tono; Rosiska, Evan (Computer Science and Industrial Engineering, 2021)
Voice Recognition for Money Deposit Boxes is a tool that is implemented to be used as a means of activating / unlocking Money Deposit Boxes by voice, with the growing era, many technologies are developing, including security for money storage devices (Safe), The money deposit box is a tool related to the security of money depositors that uses a Voice Recognition security system, to unlock the door of the Money Deposit Box with the Vocie Recognition sensor module, to detect the owner's voice. The components used to design this tool require several kinds of main devices used such as Arduino Uno as a command signal distribution tool, Voice recognition as a module that stores the input voice (Input), servo which acts as a locking device, and breadboard used to connect devices. designed, in this study it is very mandatory to have Arduino IDE software in order to be able to fill in the code or so-called commands to the microcontroller located on the Arduino Uno board, based on the tool presented is a method to unlock the money deposit box by identifying the voice of the owner